Anticoagulation Therapy (Springer International Publishing, 2018)
This book presents the latest evidence and guidelines supporting the use of anticoagulant therapy for various clinical scenarios. The field of anticoagulation therapy is evolving rapidly, particularly since the arrival and widespread adoption of direct oral anticoagulants. Organized in two parts, this book reviews the pharmacologic properties of various anticoagulants and details the clinical applications of anticoagulant therapy. Drugs such as warfarin and unfractionated heparin, as well as parenteral and direct oral anticoagulants are discussed in terms of their pharmacokinetics, drug-disease interactions, dosing strategies, and risk considerations. Clinical applications of anticoagulant therapy in disorders such as acute coronary syndromes, atrial fibrillation, and thrombophilia and in special populations such as pregnant women, the elderly, and in the patient with cancer are highlighted. Clinical vignettes, algorithms, clinical pearls, and self-assessment questions are integrated throughout the book. Featuring contributions from authorities in the field, Anticoagulation Therapy is an essential resource for cardiologists, vascular medicine specialists, hematologists, internists, and all other healthcare professionals who prescribe anticoagulants.